2008
DOI: 10.1136/jme.2008.025015
|View full text |Cite
|
Sign up to set email alerts
|

The use of legal guardians and financial powers of attorney among home-dwellers with Alzheimer’s disease living with their spousal caregivers

Abstract: We conducted a cross-sectional survey of a random sample of 1943 spouses of home-dwellers with Alzheimer's disease (AD) to examine the prevalence of court-appointed guardians or financial powers of attorney for persons with AD, related factors and the need for information about these issues among caregiving families. The questionnaire consisted questions on variables of demographic characteristics, disability, symptoms and care needs of the person with dementia, the strain of caregiving, the use of court-appoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Although the law makes it clear that social and health care professionals have a responsibility to inform their clients also of the basic legal and social security options, our studies indicate that most professionals do not regard the provision of such counselling to be part of their duties. Furthermore, according to a study carried out in 2008, only some 10% of families involved in informal care had discussed with their doctor the legal measures involved in planning for the future, although almost 50% expressed a wish to do so (Raivio et al, 2008). Another study revealed that 59% of caregivers felt that there was a need to discuss advanced care planning with their doctor but only 6% reported having had a discussion of this kind (Laakkonen, Raivio, Eloniemi-Sulkava, Tilvis, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the law makes it clear that social and health care professionals have a responsibility to inform their clients also of the basic legal and social security options, our studies indicate that most professionals do not regard the provision of such counselling to be part of their duties. Furthermore, according to a study carried out in 2008, only some 10% of families involved in informal care had discussed with their doctor the legal measures involved in planning for the future, although almost 50% expressed a wish to do so (Raivio et al, 2008). Another study revealed that 59% of caregivers felt that there was a need to discuss advanced care planning with their doctor but only 6% reported having had a discussion of this kind (Laakkonen, Raivio, Eloniemi-Sulkava, Tilvis, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, giving information and advice about legal issues of clear relevance to people with dementia is an important part of counselling (Wackerbarth & Johnson, 2002). Such advice may focus on legal matters involving social security and patients' rights (Herring, 2009b;Raivio et al, 2007) as well as guardianship services or later life legal planning (Raivio, Mäki-Petäjä-Leinonen, Laakkonen, Tilvis, & Pitkälä, 2008). Indeed, planning for the future is an essential part of anticipating the progression of dementia.…”
Section: Need For Counselling and Supportmentioning
confidence: 99%
“…Our participants were older with more comorbidities than participants in earlier studies [1,5,7,8,[21][22][23][24][25], which also included a wide range of people having very mild to very severe dementia. However, people participating in our trials have less severe dementia and use more often antidementia medications than those in large epidemiological studies [1,[25][26][27]. Furthermore, the caregivers in our study are younger and better educated than those in Finnish epidemiological study [26].…”
Section: Discussionmentioning
confidence: 68%
“…Court decisions about a person's competence have far-reaching consequences which include restrictions on that individual's liberty and civil rights. This is especially true for older adults (Kane, 2002;Kapp, 1999;Moye et al, 2013;Raivio, Maki-Petaja-Leinonen, Tilvis, & Pitkala, 2008).…”
Section: Competencementioning
confidence: 93%